Determinants of gender disparities in financial inclusion: insights from Tanzania - Mndolwa, Florence D (Research of GSB, 2018)
This study uses a nationally representative sample of individuals from Finscope survey 2013 to empirically investigate the determinants of gender disparities in financial inclusion in Tanzania. Using logit regression, the study tests whether an individual's gender affects financial inclusion. Subsequently the study evaluates the relationship between individual's characteristics and the uptake of financial services and products by gender. The results provide evidence to suggest that gender disparities in financial inclusion are only prevalent in the uptake to formal savings and formal credit but not access to formal financial accounts and mobile money accounts. Being a woman decreases the likelihood of saving while increasing the likelihood of borrowing at a formal financial institution by 17% and 2% respectively. Gender disparities in financial inclusion in Tanzania are caused by women being poorer, less educated, less employed, and more dependent than men. More women than men have no formal education hence decreasing their likelihood of accessing formal financial accounts by 58.4%. Employment is the strongest determinant increasing women's financial inclusion by 25% however fewer women are formally employed. While women have a higher propensity to save than men, they lack independence to make financial decisions, have lower financial and digital literacy and have lower mobile phone ownership to access mobile money accounts. The study recommends the Tanzania National Council for Financial Inclusion (TNCFI) to; incorporate gender targets in the financial sector and encourage gender mainstreaming in other sectors; and through engagement with other stakeholders, scale up informal financial services by integrating them with digital platforms to increase access to formal accounts. Finally, it is recommended that TNCFI boosts implementation of the National Financial Education Framework in efforts to increase women's financial capabilities and empower them to take up formal financial services.